If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 5(x + 3) Reorder the terms: 2(-2 + x) = 5(x + 3) (-2 * 2 + x * 2) = 5(x + 3) (-4 + 2x) = 5(x + 3) Reorder the terms: -4 + 2x = 5(3 + x) -4 + 2x = (3 * 5 + x * 5) -4 + 2x = (15 + 5x) Solving -4 + 2x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + 2x + -5x = 15 + 5x + -5x Combine like terms: 2x + -5x = -3x -4 + -3x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + -3x = 15 + 0 -4 + -3x = 15 Add '4' to each side of the equation. -4 + 4 + -3x = 15 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = 15 + 4 -3x = 15 + 4 Combine like terms: 15 + 4 = 19 -3x = 19 Divide each side by '-3'. x = -6.333333333 Simplifying x = -6.333333333
| 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 | | 6x-27=4x+12 | | cx+5=dx-3 | | 5+2(x+1)=2n | | 9y+13=30 | | w^2-11=2-5w^2 | | 6x+40=8x-20 |